1981
DOI: 10.1042/bj1930799
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of action of 6-mercaptopurine. Interaction with copper and xanthine oxidase

Abstract: Interaction between 6-mercaptopurine, Cu2+ and the enzyme xanthine oxidase (EC 1.2.3.2.) was examined. Whereas Cu2+ was found to inhibit the enzyme, 6-mercaptopurine could protect as well as reverse the enzyme inhibition produced by the metal ion. The formation of a complex between 6-mercaptopurine and Cu2+ seems to be responsible for the observed effect. Job's [(1928) Ann. Chem. 9, 113] method has shown the composition of the complex to be 1:1. The apparent stability constant (log K value), as determined by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Some 6-MP is converted to nucleotide derivatives of 6-thioguanine (6TG) by the sequential actions of inosinate dehydrogenase and xanthylate aminase, converting thioinosinic acid to thioguanylic acid. Preclinical tumors resistant to 6-MP often cannot convert 6-MP to thioinosinic acid (26,27). However, many mechanisms of resistance to 6-MP have been identified, particularly in human leukemias (28).…”
Section: Introductionmentioning
confidence: 99%
“…Some 6-MP is converted to nucleotide derivatives of 6-thioguanine (6TG) by the sequential actions of inosinate dehydrogenase and xanthylate aminase, converting thioinosinic acid to thioguanylic acid. Preclinical tumors resistant to 6-MP often cannot convert 6-MP to thioinosinic acid (26,27). However, many mechanisms of resistance to 6-MP have been identified, particularly in human leukemias (28).…”
Section: Introductionmentioning
confidence: 99%
“…Their physiological functions are partly related to their interaction with metal ions [1,2]. Therefore, it is of special importance to investigate their electrochemical behavior on metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that their physiological roles are partly related to the oxidation-reduction of -SH and -S-Sgroups, as well as the interaction of -SH/-S-S-with metal ions [4][5][6][7]. Most of these compounds exhibit electroactivity.…”
Section: Introductionmentioning
confidence: 99%